Reproducibility of task description questionnaire among brazilian pregnant workers - Rosa, Priscila Cibils da; Moreira, Géssica Maria; Mochizuki, Luís; Sperandio, Fabiana Flores (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The increase in the number of pregnant women working to the end of gestation has attracted interest in studying the effects of work on maternal fetal health. A task description questionnaire (TDQ) was developed to evaluate pregnant women and labor tasks performed in this period. Objectives: The purpose of the study was to evaluate the reproducibility of the TDQ and its questions regarding the labor tasks performed by pregnant workers. Methods: Test-retest reproducibility was performed with data collected at seven-day intervals in 37 pregnant women. A Spearman test and κ coefficients were calculated for test-retest agreement. Results: With regard to κ, the results showed good to total agreement for questions 3 and 4. The Spearman correlation was excellent to moderate (for questions 5 and 6). Conclusions: The results of the reproducibility of the TDQ reflected the good understanding of this tool, because it was simple, easy and fast to apply. A TDQ can detect the need for changes in the occupational environment of pregnant workers. This ensures the examination of maternal fetal health and safety.